Food Memory and Food Identity of Educated People Migrating from Turkey for Work or Higher Education (Journal of Advanced Research in Social Sciences, 2022)
This qualitative study aims to understand the food memory and food identity of a group who emigrated from Turkey to North Carolina for education or for work 30-40 years ago. For this purpose, one-to-one in-depth interviews were conducted with 14 persons, 12 women and 2 men living in North Carolina using the Zoom application. In the interviews, participants said that they are connected to their roots with their homeland’s food, that is Turkish food. They had not given up on cooking and eating Turkish dishes. The memories they described are so to say proving food memory and food identity concepts which are searched in migration studies. These are sub-topics of food anthropology. Also, they have a real effort to serve Turkish food to their non-Turkish friends, neighbours and this effort seems to be an attempt to show their identity with their food. Besides, it can also be said that they were influenced by other cuisines and experienced a cultural diffusion.